2016
DOI: 10.1039/c5sm01726b
|View full text |Cite
|
Sign up to set email alerts
|

Electric field generation of Skyrmion-like structures in a nematic liquid crystal

Abstract: We report the generation of stable Skyrmion-like structures in a thin nematic liquid crystal film on chemically patterned patchy surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…The preferred orientation of the BP is thus mediated by the strain imposed by a patterned surface, and the generality of this concept is established by designing different patterns that stabilize different orientations along the BPII (100) , BPII (110) and BPII (111) crystallographic lattice planes. In this context, we hasten to point out that Cattaneo et al 41. have shown that square-like patchy patterns can be used to induce formation of Skyrmion-like phases in non-chiral liquid crystals—the molecules of this phases form chiral twists but the entire phase does not possess a crystalline symmetry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preferred orientation of the BP is thus mediated by the strain imposed by a patterned surface, and the generality of this concept is established by designing different patterns that stabilize different orientations along the BPII (100) , BPII (110) and BPII (111) crystallographic lattice planes. In this context, we hasten to point out that Cattaneo et al 41. have shown that square-like patchy patterns can be used to induce formation of Skyrmion-like phases in non-chiral liquid crystals—the molecules of this phases form chiral twists but the entire phase does not possess a crystalline symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we hasten to point out that Cattaneo et al . 41 have shown that square-like patchy patterns can be used to induce formation of Skyrmion-like phases in non-chiral liquid crystals—the molecules of this phases form chiral twists but the entire phase does not possess a crystalline symmetry. A closer inspection of the LC texture in the proximity of our BPII (111) and BPII (110) interfaces, also reveals the formation of Skyrmion structures reminiscent of those observed by these authors (see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such behaviour is also reported to be observed experimentally. 72 The free energy of these induced boojum states is several 10% higher than the free energy of the HAN configuration.…”
Section: Boojum Nematic Configurationmentioning
confidence: 95%
“…9,10,[21][22][23][24][25] It has been shown that the classification of such topological systems is given by topological conservation laws and depends on topological invariants, such as knot polynomials and the crossing number of the knots. 26,27 Complex nematic fluids are shown to stabilise a variety of topological structures spanning from solitonic structures like skyrmions, merons, torons and hopfions [28][29][30][31][32][33][34][35] to different forms of defect points and lines. [36][37][38] These topological structures can form either spontaneously or by localized inclusions, such as with colloidal particles.…”
Section: Introductionmentioning
confidence: 99%